TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCABULAN ANAK DI BAWAH UMUR DI KUTAI BARAT BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Rifka Handayani Gamas (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractThe rapid development of current information and technology has become one of the triggers for criminal acts, including criminal acts of sexual abuse against minors. A molestation is an act carried out by someone who is driven by a sexual desire to do things that can arouse lust, thus giving satisfaction to him. Most perpetrators of obscene acts are in the neighborhood around the victim. The culprit is also very diverse, namely, adults and fellow underage children, and victims can be a boy or a girl. The method used in this study is the Empirical method. The problem that the author discussed in this paper is the factor that led to the crime of sexual abuse of minors in Kutai Barat Regency, the application of material criminal law for perpetrators of criminal acts of sexual abuse of minors based on Law Number 35 of 2014 concerning Child Protection and efforts made by law enforcement officials to tackle the crime of molesting minors in Kutai Barat District. Based on the results of the study, it can be concluded that there are factors that lead to criminal acts of sexual abuse against minors in Kutai Barat regency, namely technological developments, widespread pornographic content, less harmonious husband-wife relations, and most of them caused by the influence of liquor (alcohol). Police officers have the main task of receiving reports and complaints from the public in the event of a crime, conducting an investigation and investigation. Application of materially criminal law for perpetrators of criminal acts of sexual abuse against minors based on Article 76E and Article 82 of Law Number 35 the Year 2014 concerning Child Protection and to combat crimes especially criminal acts of sexual abuse against minors of Community Development Unit (Sat Binmas) do socialization / counseling. The main targets are children in the PPA (Children's Development Center) in churches and among middle school, high school, and vocational students in public and private schools. Counseling/socialization is not only for children and adolescents but for all levels of the general public.